The effect of Ce on the high temperature oxidation properties of a Fe–22%Cr steel: microstructural investigation and EELS analysis. (January 2015) - Sattari, M.; Sachitanand, R.; Froitzheim, J.; Svensson, J. E.; Jonsson, T.
Abstract : The effect of a 10 nm Ce coating layer on long term oxidation behaviour (up to 3000 hours) of a Fe–22%Cr ferritic stainless steel for solid oxide fuel cell (SOFC) interconnect application is investigated. Scanning transmission electron microscopy (STEM) and electron energy loss spectroscopy (EELS) analysis showed segregation of Ce to the grain boundaries of Cr, Mn spinel layer adjacent to the scale-gas interface. The findings in this study are in line with the grain boundary blocking model for the Ce effect mechanism. However, segregation of Ce was observed at the grain boundaries of the (Cr, Mn) spinel in the vicinity of the scale-gas interface. No evidence of Ce segregation was found in the grain boundaries of the chromia layer, neither any Ce rich particle was observed in the chromia layer after longer exposure times.